THE MAIN FACTORS THAT ESTABLISH THE WELFARE OF CORPORATE SOCIAL RESPONSIBILITY’S BENEFICIARIES OF PERTAMINA FOUNDATION - Gema, Alfatira; Pangestuty, Farah Wulandari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Social welfare has grown to be a crucial component of national development policies. At the same time, important to aware that less prosperous communities, including the homeless, street children, child labourers, and migrant workers, are the primary recipients of social assistance. Social welfare is a condition of human life created when various social problems can be managed properly. This understanding places social welfare as the goal of development activities. Corporate social responsibility is one of the programs considered as one that can contribute to the welfare of society. This research aims to analyse, confirm, and then conduct research to gather facts and conclusions regarding the main factors that establish the welfare of corporate social responsibility beneficiaries of the Pertamina Foundation. This quantitative research using surveys through google form to Pertamina Foundation's beneficiaries using a Likert scale. This research also uses SEM methods with LISREL as a tool. The result shows that CSR- Economic Aspect (X1), CSR-Social Aspect (X2) and CSR-Environmental Aspect (X3) positively and significantly influences the welfare of Pertamina Foundation’s beneficiaries.